Coordinated Emergence of Hippocampal Replay and Theta Sequences during Post-natal Development - Muessig, Laurenz (Curr Biol, 2019)
Hippocampal place cells encode an animal’s current position in space during exploration [1]. During sleep, hippocampal network activity recapitulates patterns observed during recent experience: place cells with overlapping spatial fields show a greater tendency to co-fire (“reactivation”) [2], and temporally ordered and compressed sequences of place cell firing observed during wakefulness are reinstated (“replay”) [3, 4, 5]. Reactivation and replay may underlie memory consolidation [6, 7, 8, 9, 10]. Compressed sequences of place cell firing also occur during exploration: during each cycle of the theta oscillation, the set of active place cells shifts from those signaling positions behind to those signaling positions ahead of an animal’s current location [11, 12]. These “theta sequences” have been linked to spatial planning [13]. Here, we demonstrate that, before weaning (post-natal day [P]21), offline place cell activity associated with sharp-wave ripples (SWRs) reflects predominantly stationary locations in recently visited environments. By contrast, sequential place cell firing, describing extended trajectories through space during exploration (theta sequences) and subsequent rest (replay), emerge gradually after weaning in a coordinated fashion, possibly due to a progressive decrease in the threshold for experience-driven plasticity. Hippocampus-dependent learning and memory emerge late in altricial mammals [14, 15, 16, 17], appearing around weaning in rats and slowly maturing thereafter [14, 15]. In contrast, spatially localized firing is observed 1 week earlier (with reduced spatial tuning and stability) [18, 19, 20, 21]. By examining the development of hippocampal reactivation, replay, and theta sequences, we show that the coordinated maturation of offline consolidation and online sequence generation parallels the late emergence of hippocampal memory in the rat.